Analisis Postur Kerja Terhadap Kesehatan dan Keselamatan Kerja dengan Metode Rosa (Rapid Office Strain Assesment) di PT Angkasa Pura 1 Juanda Surabaya - Musyaffa, Akmal Fikri Faaiz; Rusindiyanto, Rusindiyanto (Universitas Batanghari Jambi, 2024)
Juanda Airport in Surabaya is an airport with a high level of activity. This study aims to analyze and assess the level of risk of workers' posture to health and work accidents in the work environment of PT Angkasa Pura 1 Juanda Airport Surabaya using the ROSA (Rapid Office Strain Assessment) method. The results of the study are assessment of work posture using the ROSA method that employees with a score of 4 are 1 person, score 5 are 4 people, score 6 are 6 people, score 7 are 7 people, score 8 are 4 people, score 9 as many as 3 people with a risk category. From this value, 1 employee is not at risk and 24 workers have a dangerous risk because it has a value of more than 5.